Development of Marker-Based Augmented Reality Application for Learning Hijaiyah Letters in Tahfiz Schools - Nasution, Mutiara Akbar; Ritonga, Rama Prameswara; Ahlun, Zaid; Lubis, Muhammad Rafli Taufiq (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
Learning Hijaiyah letters is an early stage in Islamic education, but conventional methods are often less interesting for children. Augmented Reality (AR) offers an innovative solution that can increase interactivity in the learning process. This study aims to develop and test a marker-based AR application for learning Hijaiyah letters in Tahfiz Schools. This application allows users to scan markers to display Hijaiyah letters in three dimensions and hear their pronunciation. The research method used is Research and Development (R&D) with a Waterfall model that includes needs analysis, design, implementation, and testing. Evaluation was carried out through Blackbox Testing for functionality and user questionnaires. The test results showed that this application functions well, is easy to use, and is attractive to students. The majority of users stated that the appearance and sound of the application are of good quality. Augmented Reality technology has been proven to improve the learning experience to be more interactive and effective. This study is expected to be a reference for the development of AR applications in Islamic education.